HUBUNGAN TINGKAT KEPADATAN LALAT ( Musca domestica ) DENGAN KEJADIAN DIARE PADA ANAK BALITA DI PEMUKIMAN SEKITAR TEMPAT PEMBUANGAN AKHIR SAMPAH NAMO BINTANG KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG TAHUN 2012 - Merylanca Manalu; Irnawati Marsaulina; Taufik Ashar (Lingkungan dan Kesehatan Kerja, 2013)
Correlation between the density of flies (Musca domestica) with the incidence of diarrhea in children under five years in the settlements around the Disposal Area of Garbage Namo Bintang Kecamatan Pancur Batu Kabupaten Deli Serdang in 2012. Diarrhea is a disease indicated by the increase in number of defecation  more than usually (three or  more a day)  for less than 14 days associated with the changes in shape and consistency of feces of the patients. The present study intented to know the correlation between  the density rate of flies and the incidence of diarrhea around the Disposal Area of Garbage. The design of the study was an analytic  descriptive using cross-sectional  design  with 60 samples of household with infants. The data were collected by measuring the density rate of flies, interview, and observation. The data were analyzed by using univariate statistic test and then followed by bivariate test by using chi-square (X2). The result of the study showed that there was a  significant correlation between the density of flies and  the  incidence of diarrhea in infants. It could be indicated by the sig-p (0.0001) ≤ 0.05. The other factors that had significant  correlation to the incidence of diarrhea included attitude of the mothers in washing their hands p=0.0001 ((p≤0.05),  their attitude in closing the food p=0.0001 (p≤0.05), using the clean water p=0.0001 (p≤0.05), and using the  drinking water p=0.0001 (p≤0.05). The conclusion of the study was that there was a   correlation between the density of flies and  the  incidence of diarrhea in infants. Therefore, it was suggested to the mothers of infant to install the screen on the window and  ventilation,  improving the  sanitation  around  the Disposal Area of Garbage.   Key words: Density of flies, Diarrhea, Garbage